Patterns of Eosinophilia in Cardiac Patients and its Association with Endomyocardial Disease in a Tertiary Care Hospital at Peshawar - Azeem, Rashid (International Journal of Pathology, 2023)
Introduction: Eosinophilia, which can be categorized as mild, moderate and severe form on the basis of increasing eosinophil counts, might be responsible for a wide range of cardiac manifestations, varying from a simple myocarditis to a severe state like endomyocardial fibrosis. Eosinophils are involved in the pathogenesis of a variety of cardiovascular disorder like Loffler endocarditis, eosinophilic granulomatosis with polyangitis (EGPH) and hyper eosinophilic syndrome (HES).Objectives: To determine the patterns of eosinophilia in cardiac patients and its association with endomyocardial diseases in eosinophilc patientsMaterial and Methods: This cross-sectional analytical study was conducted in hematology Department of Peshawar institute of Cardiology after approval from hospital ethical and research committee. All 70 patients were subjected to detailed history and clinical examination. Investigation like CBC, Chest X-ray, ECG, Echo, Angiography findings were used to monitor patient’s clinical status. Data is analyzed using SPSS version 25 and MS ExcelResults: Out of 70 patients in our study, a total of 66 patients (94%) shows evidence of cardiac manifestations. In our study we have observed a number of abnormal ECG patterns like T wave changes, loss of R wave, sinus bradycardia with LVH strain and ST wave abnormality. Abnormal echocardiographic findings were observed like valvular abnormalities (in 45.7%), RWMA abnormalities (in 5.7%), isolated ventricular dysfunction (in 21.4%). We further noted abnormal coronary angiography findings ranging from single vessel to multi vessel occlusions. Chi square test was applied showing significant P value of 0.001Conclusions: Increased eosinophilic count as a laboratory parameter in cardiac patients may be a sign of endomyocardial damage helping the cardiologist to intervene more aggressively then routine approach